Leukemic Infiltration Of The Testes - Sugandhi N. S.; Iskandar Wahidijat; A. H. Markum; S. Muslichan (Paediatrica Indonesiana, 1974)
The present report describes leu-kemic infiltration of the testes in a6 1/2-year-old boy suffering from acu-te lymphoblastic leukemia duringbone marrow and hematologic remis-Sion.